NAMING CIVILIZATION: METHODOLOGICAL IMPLICATIONS OF TERMINOLOGY IN THE STUDY OF ISLAM - Labib Elmuna; Muhammad Ismail; Nidaa Kaamilah Husna (Senarai: Journal of Islamic Heritage and Civilization, 2026)
This study explores the conceptual and methodological complexity in the term Islamic Civilization and its related designations, Muslim Civilization and Civilization in the Islamic World. It argues that differences in terminology are not only semantic discourse but reflect distinct epistemological orientations and methodological frameworks for understanding the historical and intellectual trajectory of Islam and its adherents. Methodologically, this research employs a descriptive literature review centered on Christian Sahner’s formulation in “What is Islamic History?” Through a close textual reading of Sahner’s work, the study critically examines its conceptual foundations and historiographical implications, while placing it in dialogue with Marshall Hodgson’s notion of “Islamicate Civilization” and Shahab Ahmed’s interpretive approach to the importance of being Islamic. This comparative approach enables the study to identify convergences, divergences, and underlying epistemological assumptions in contemporary discussions of Islamic civilization. The discussion reveals that the term Islamic Civilization emphasizes normative ideals derived from al-wahy, whereas Muslim Civilization represents the historical embodiment of these ideals in human experience. At the same time, Civilization in the Islamic World captures the broader intercultural and transregional synthesis of ideas that shaped Islamic societies. By situating these frameworks in dialogue, the study seeks to demonstrate how terminological precision shapes the methodological direction of civilizational studies and calls for a more integrative paradigm, one that acknowledges Islam’s spiritual core while embracing the diversity and dynamism of its historical manifestations.